2013
DOI: 10.1016/j.steroids.2013.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Non-classic congenital adrenal hyperplasia

Abstract: Nonclassic congenital adrenal hyperplasia (NCAH) due to P450c21 (21-hydroxylase deficiency) is a common autosomal recessive disorder. This disorder is due to mutations in the CYP21A2 gene which is located at chromosome 6p21. The clinical features predominantly reflect androgen excess rather than adrenal insufficiency leading to an ascertainment bias favoring diagnosis in females. Treatment goals include normal linear growth velocity and "on-time" puberty in affected children. For adolescent and adult women, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 78 publications
0
44
0
6
Order By: Relevance
“…Nevertheless, they have a partial cortisol insufficiency [14,32,51], mostly very mild, but up to one-third of them have an ACTH-stimulated cortisol level below 400 nmol/L and 60 % a level of less than 500 nmol/L. It has been suggested that a stimulated cortisol level of less than 500 nmol/L may justify daily glucocorticoid supplementation [52]. At least a liberal prescription of glucocorticoids for use during severe illness could be recommended for those with a suboptimal stimulated level.…”
Section: Treatmentmentioning
confidence: 99%
“…Nevertheless, they have a partial cortisol insufficiency [14,32,51], mostly very mild, but up to one-third of them have an ACTH-stimulated cortisol level below 400 nmol/L and 60 % a level of less than 500 nmol/L. It has been suggested that a stimulated cortisol level of less than 500 nmol/L may justify daily glucocorticoid supplementation [52]. At least a liberal prescription of glucocorticoids for use during severe illness could be recommended for those with a suboptimal stimulated level.…”
Section: Treatmentmentioning
confidence: 99%
“…The reported incidence is 1:8900 [4] in Argentina, between 1:15,000 and 1:16,000 in Europe and North America and 1:19,000 in Japan [5][6][7]. In contrast to the classic defect, the incidence of the non-classic defect (NCCAH) is assumed to be 1:1000 [8]. Due to intrauterine high androgen levels, the external genitalia of the female neonate with classic CAH is already virilized at birth, whereas the internal genitalia is always female.…”
Section: Introductionmentioning
confidence: 99%
“…Whether all non-classic congenital adrenal hyperplasia patients require glucocorticoid replacement therapy remains uncertain. However, an adrenocorticotropic hormone-stimulated cortisol response of less than 18 μg/dL may justify daily glucocorticoid replacement therapy, as reported previously (3). As the patient in this study had a history of symptomatic hyponatremia associated with gastroenteritis, glucocorticoid replacement therapy would be indicated.…”
Section: Introductionmentioning
confidence: 58%
“…Non-classic congenital adrenal hyperplasia due to 21-hydroxylase deficiency is one of the most common genetic disorders with a prevalence of approximately 1 in 100 to 1,000 people (1)(2)(3). In Japan, its prevalence has been reported to be only 1 in 2 million people (4).…”
Section: Introductionmentioning
confidence: 99%